(untitled) (Communications in Computational Physics, 2010)
We investigate the critical nucleus and equilibrium morphologies during precipitation of a second-phase particle in a solid. We show that a combination of diffuse-interface description and a constrained string method is able to predict both the critical nucleus and equilibrium precipitate morphologies simultaneously without a priori assumptions. Using the cubic to cubic transformation as an example, it is demonstrated that the maximum composition within a critical nucleus can be either higher or lower than that of equilibrium precipitate while the morphology of an equilibrium precipitate may exhibit lower symmetry than the critical nucleus resulted from elastic interactions.